PENGARUH WORD of MOUTH, DIGITAL MARKETING, BRAND AWARENESS TERHADAP COSTUMER LOYALTY PADA ARTIS BARU SEVEN MUSIC INDONESIA - Sarida Minarni; Kurnia Sari Dewi (Universitas Prof. Dr. Moestopo (Beragama), 2023)
The development of Indonesian music every year shows considerable growth. Indonesian music has become a host for music listeners in the country. One of the reasons for this development is that technology is developing rapidly and helping musicians produce and disseminate their work. The purpose of this research is to find out the influence of Word of Mouth, Digital Marketing, Brand Awareness on Customer Loyalty for new artists, Seven Music Indonesia. Respondents in this study were listeners to Swaragama Jogjakarta radio who listened to the Zona Persada program every Monday - Friday at 19.00 - 21.00 in October - November 2020 who conducted interactive (request) songs. The number of respondents in this study was set at 186 respondents. This research gives the results: 1) Word of Mouth has a significant direct effect on Customer Loyalty, 2) Digital Marketing has a positive influence on Customer Loyalty, 3) Brand Awareness has a positive influence on Customer Loyalty, 4) Word of Mouth, Digital Marketing, Brand Awarness has a significant influence on Customer Loyalty for Seven Music Indonesia's New Artists.